Positioning of nasobiliary tube using magnet-loaded catheters - Watanabe, Seitaro; Sato, Takamitsu; Kato, Shingo; Hosono, Kunihiro; Kobayashi, Noritoshi; Nakajima, Atsushi; Kubota, Kensuke (Endoscopy, 2013)
Background and study aims: In endoscopic nasobiliary drainage (ENBD), repositioning the catheter from the mouth to the nose is complicated. We devised a method using catheters with magnets and verified its utility and safety.Patients and methods: We prospectively enrolled 20 patients undergoing ENBD at Yokohama City University Hospital.Results: The procedures were successful in all 20 cases and no case required a change of operators to a senior doctor. The mean time for the procedure was 36.6 seconds. The emetic reflex was induced 0.5 times on average using the magnet method. The mean X-ray exposure time was 29.6 seconds. No complications occurred.Conclusions: The magnet-loaded catheter method for positioning the ENBD catheter before finally leading it through the nose took little time and was performed successfully and safely. Therefore, the magnet method could become the first choice among techniques for ENBD catheter placement.